Water-based printing coating as well as preparation method and application thereof
By modifying silicon/aluminum oxide complexes and amino polyethylene alcohol, and an adhesive promoters such as the water dioxide complexes and amino -based polyethylene alcohol, the water -based printing coating is solved in the non -extreme Insufficient attachment properties and abrasion resistance on nature or smooth substrates achieve the effect of high adhesion and abrasion resistance.
Patent Information
- Application Number
- CN202411814809.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The existing water-based printing coatings have poor adhesion performance on non-polar or smooth substrates, are prone to peeling or stratification, and are not well-behaved and difficult to resist mechanical stress and friction.
The use of specific water -based resin emulsion and adhesion to promote agents. Water -based resin emulsion combines the combination of silicon/aluminum oxide complexes and amino polyethylene glycols on the surface to form a network structure of intensity and abrasion resistance of coating sex.
It significantly improves the adhesion and wear resistance of water -based printing coatings, extend the service life of the product, while maintaining green environmental protection and low VOC content.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a water-based printing coating and a preparation method and application thereof. Background Art
[0002] Printing coatings are an integral part of modern printing technology, playing a key role in improving the quality and functionality of printed materials. From books and magazines to packaging materials, from advertising posters to artwork reproductions, almost any item that needs to be printed can have its physical properties and visual appeal enhanced by the use of different printing coatings. Printing coatings can be divided into many types, including water-based coatings, oil-based coatings, UV ultraviolet light curing coatings, etc., each type has its own unique advantages and scope of application. For example, water-based coatings are particularly suitable for children's books and food packaging due to their environmentally friendly and non-toxic characteristics; while UV coatings are known for their fast drying, high-intensity gloss and excellent wear resistance, making them very suitable for high-end packaging and promotional materials. In order to achieve the best coating effect, printing coatings can be applied to the substrate through a variety of methods, such as coating, spraying, roller transfer, screen printing, etc., to ensure that the coating is uniform and consistent, and closely combined with the substrate, thereby improving the wear durability and anti-fouling ability of the printed matter.
[0003] With the increasing awareness of environmental protection, the printing industry has higher and higher requirements for green printing technology. Environmentally friendly coatings must reduce the emission of volatile organic compounds (VOCs) and reduce energy consumption while ensuring that product quality is not affected. At present, water-based printing coatings are relatively poor in adhesion performance, especially on non-polar or smooth substrates, such as plastics and metals. The coating film is prone to peeling or stratification, which not only affects the aesthetics of the product, but also reduces its protective function. The coating film formed by water-based coatings is not very tough and is prone to cracks when subjected to mechanical stress such as bending and folding, resulting in poor durability. In addition, water-based coatings also have poor wear resistance and are difficult to resist friction and scratches in daily use. This is an obvious disadvantage for products that require frequent contact, such as packaging materials and promotional materials.
[0004] In order to overcome the above-mentioned shortcomings of water-based printing coatings, various methods have been used in the prior art to improve these properties. For example, by optimizing the formula and adding functional additives such as crosslinkers, plasticizers and surfactants, the adhesion and toughness of water-based coatings can be improved to a certain extent; crosslinkers can form a three-dimensional network structure during the drying process of the coating film, enhance the mechanical strength and chemical resistance of the coating film, plasticizers help to improve the flexibility and impact resistance of the coating film, and surfactants can reduce the surface tension of water, promote the coating to better wet the substrate, thereby improving adhesion. Secondly, the substrate can also be pre-treated by corona treatment or flame treatment to increase the energy of the substrate surface and improve the affinity with the coating. For materials that are difficult to adhere to, such as plastics, primer or coating treatment can provide a better adhesion interface for water-based coatings. However, despite the above measures, there are still some shortcomings, such as adding too much additives will cause the hardness of the coating film to decrease, affecting its wear resistance and glossiness, and the substrate pretreatment increases the production steps and costs, which has a certain impact on the efficiency of large-scale production. Therefore, there is an urgent need for a water-based printing coating with low VOC content and excellent adhesion and wear resistance. Summary of the invention
[0005] The purpose of the present invention is to provide a water-based printing coating, which is not only green and environmentally friendly, has a low VOC content, but also has excellent adhesion and wear resistance by using a specific water-based resin emulsion and an adhesion promoter. The present invention also provides a preparation method of the water-based printing coating and its application in digital inkjet printing.
[0006] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a water-based printing coating, comprising the following raw materials in parts by weight: 55-65 parts by weight of aqueous resin emulsion, 1-2 parts by weight of adhesion promoter, 0.7-1.2 parts by weight of aqueous dispersant, 0.3-0.6 parts by weight of aqueous defoamer, 1-3 parts by weight of film-forming aid, 30-40 parts by weight of water.
[0007] Preferably, the method for preparing the aqueous resin emulsion comprises the following steps: 5-8 parts by weight of polyvinyl alcohol, 2-5 parts by weight of epichlorohydrin and 80-100 parts by weight of hydrochloric acid are mixed, heated and stirred, centrifuged and dried to obtain an intermediate; 3-5 parts by weight of the intermediate, 0.03-0.06 parts by weight of tetrabutylammonium bromide and 40-60 parts by weight of ammonia water are mixed, and then 15-25 parts by weight of ethylenediamine are added, heated and stirred, centrifuged and dried to obtain amino polyvinyl alcohol; 8-12 parts by weight of tetraethyl orthosilicate, 20-30 parts by weight of aluminum nitrate and 100-150 parts by weight of anhydrous ethanol are mixed to obtain a mixed solution, and the mixed solution is added to 150-200 parts by weight of aqueous ammonia under stirring conditions for reaction, filtered, dried, and calcined to obtain a silica / alumina composite; 5-7 parts by weight of the silica / alumina composite are mixed with 40-60 parts by weight of water, stirred, and then 1-1.5 parts by weight of 3-acrylamidopropyl tris(trimethylsiloxy)silane are added, the temperature is raised and stirring is continued, cooled, filtered, and dried to obtain a surface-modified silica / alumina composite; 0.2-0.5 parts by weight of sodium lauryl sulfate, 0.08-0.12 parts by weight of polyvinyl pyrrolidone and 10-20 parts by weight of water are mixed, then 2-5 parts by weight of surface modified silicon dioxide / aluminum oxide composite and 1-4 parts by weight of amino polyvinyl alcohol are added for ultrasonic dispersion, and then 6-8 parts by weight of ethyl methacrylate, 2-4 parts by weight of butyl acrylate and 0.05-0.15 parts by weight of ammonium persulfate are added, and heated for reaction under nitrogen atmosphere to obtain an intermediate material; 2-4 parts by weight of acrylic acid, 6-8 parts by weight of ethyl methacrylate, 1-4 parts by weight of butyl acrylate, 1-2 parts by weight of hydroxypropyl acrylate, 0.3-0.8 parts by weight of methacrylamide and 0.1-0.3 parts by weight of ammonium persulfate are mixed, heated and stirred, then 10-30 parts by weight of the intermediate material are added, stirring is continued, and cooling is performed to obtain an aqueous resin emulsion.
[0008] The aqueous resin emulsion prepared by the present invention can not only make the aqueous printing coating maintain good adhesion performance, but also further improve the wear resistance of the coating, thereby extending the service life. In the preparation process, acrylic acid, ethyl methacrylate, butyl acrylate, hydroxypropyl acrylate, and methacrylamide components are used as the matrix, and surface-modified silicon dioxide / alumina composite and amino polyvinyl alcohol are added as functional fillers, while maintaining good adhesion performance, the wear resistance of the coating is significantly improved.
[0009] First, the precursor tetraethyl orthosilicate and aluminum nitrate are used to obtain silicon dioxide / aluminum oxide composite by sol-gel method. Compared with silicon dioxide, the introduction of aluminum oxide to form a composite can assist in enhancing the wear resistance of the filler, and 3-acrylamide propyl tris (trimethylsiloxy) silane is used to surface modify the silicon dioxide / aluminum oxide composite, which not only improves its surface activity, but also enhances the bonding force and adhesion between the emulsion matrix component, effectively preventing the filler from falling off during use, thereby further improving the wear resistance of the coating. Secondly, the present invention uses the surface-modified silicon dioxide / aluminum oxide composite as a core, using ethyl methacrylate, butyl acrylate, etc. as shell monomers, and obtains a core-shell emulsion coated on the surface by emulsion polymerization, while introducing monomers such as hydroxypropyl acrylate and methacrylamide to promote the formation of a cross-linked network in the system, and plays a fixed bonding effect on the silicon dioxide / aluminum oxide composite, and this cross-linked network not only enhances the bonding force between the composite and the matrix component, but also provides a physical protective layer, further improving the wear resistance of the coating.
[0010] In addition, amino polyvinyl alcohol is added as a reinforcing filler. After amino treatment, polyvinyl alcohol can be connected to the acrylate main chain through the polymerization of the active functional groups on the acrylate monomer and the amino group, which not only improves the flexibility and wear resistance of the coating, but also enhances the bonding performance between the components through interaction forces such as hydrogen bonds. Aminated polyvinyl alcohol has good film-forming and hydrophilic properties, so that the coating has better wear resistance while maintaining excellent adhesion properties, enhances the adhesion between the coating and the substrate, and reduces the risk of coating peeling.
[0011] Furthermore, the preparation method of the aqueous resin emulsion comprises the following steps: 5-8 parts by weight of polyvinyl alcohol, 2-5 parts by weight of epichlorohydrin and 80-100 parts by weight of 0.2-0.5wt% hydrochloric acid are mixed, stirred at 65-70°C and 100-200rpm for 40-60min, centrifuged and dried to obtain an intermediate; 3-5 parts by weight of the intermediate, 0.03-0.06 parts by weight of tetrabutylammonium bromide and 40-60 parts by weight of 0.3-0.6wt% ammonia water are mixed, and then 15-25 parts by weight of ethylenediamine are added, stirred at 65-70°C and 100-200rpm for 2-4h, centrifuged and dried to obtain amino polyvinyl alcohol; 8-12 parts by weight of tetraethyl orthosilicate, 20-30 parts by weight of aluminum nitrate and 100-150 parts by weight of anhydrous ethanol are mixed to obtain a mixed solution, and the mixed solution is added to 150-200 parts by weight of 15-18wt% ammonia water at 30-40°C and 500-700rpm for reaction for 6-8h, filtered, dried, and then calcined at 450-550°C for 2-4h to obtain a silica / alumina composite; 5-7 parts by weight of the silica / alumina composite is mixed with 40-60 parts by weight of water, stirred at room temperature and 500-700rpm for 0.3-0.6h, and then 1-1.5 parts by weight of 3-acrylamidopropyl tris(trimethylsiloxy)silane is added, the temperature is raised to 85-90°C and stirring is continued for 10-15h, cooled to room temperature, filtered, and dried to obtain a surface-modified silica / alumina composite; 0.2-0.5 parts by weight of sodium lauryl sulfate, 0.08-0.12 parts by weight of polyvinyl pyrrolidone and 10-20 parts by weight of water are mixed, and then 2-5 parts by weight of surface-modified silicon dioxide / aluminum oxide composite and 1-4 parts by weight of amino polyvinyl alcohol are added and ultrasonically dispersed for 10-20 minutes, wherein the power of the ultrasound is 100-200 W and the frequency is 20-30 kHz, and then 6-8 parts by weight of ethyl methacrylate, 2-4 parts by weight of butyl acrylate and 0.05-0.15 parts by weight of ammonium persulfate are added, and the mixture is stirred at 80-90 °C for 24 hours. 0°C, react for 5-8h under nitrogen atmosphere to obtain an intermediate material; 2-4 parts by weight of acrylic acid, 6-8 parts by weight of ethyl methacrylate, 1-4 parts by weight of butyl acrylate, 1-2 parts by weight of hydroxypropyl acrylate, 0.3-0.8 parts by weight of methacrylamide and 0.1-0.3 parts by weight of ammonium persulfate are mixed, stirred at 75-80°C and 100-200rpm for 20-40min, then 10-30 parts by weight of the intermediate material are added and stirring is continued for 1-3h, cooled to room temperature, and the pH is adjusted to neutral to obtain an aqueous resin emulsion.
[0012] Preferably, the method for preparing the adhesion promoter comprises the following steps: 20-35 parts by weight of phytic acid aqueous solution are mixed with 2-5 parts by weight of glycidyl acrylate, and then 0.1-0.3 parts by weight of tetrabutylammonium bromide and 0.03-0.05 parts by weight of hydroquinone are added, heated for reaction, extracted, and distilled under reduced pressure to obtain alkenyl grafted phytic acid; 8-12 parts by weight of hydroxypropyl acrylate, 1-3 parts by weight of isomeric tridecyl alcohol polyoxyethylene ether, and 1-2 parts by weight of γ-aminopropyl triethoxysilane are mixed, 3-6 parts by weight of alkenyl grafted phytic acid are added under a nitrogen atmosphere, stirred, and then 0.5-0.8 parts by weight of water are added, stirred continuously, and cooled to obtain an adhesion promoter.
[0013] The present invention uses hydroxypropyl acrylate, isomeric tridecanol polyoxyethylene ether, γ-aminopropyl triethoxysilane and alkenyl grafted phytic acid as raw materials to prepare an adhesion promoter, which can effectively improve the adhesion performance of water-based coatings. In the whole process, each component forms a complex three-dimensional network structure through chemical bonding and interaction, so that the adhesion promoter can not only be firmly attached to the surface of the substrate, but also can be closely combined with the film-forming resin, thereby further improving the adhesion performance of the water-based coating. Among them, the phosphate group of the alkenyl grafted phytic acid can form a strong coordination bond or covalent bond with the hydroxyl group or oxide layer on the surface of the substrate to enhance adhesion, and the unsaturated double bond can participate in the cross-linking reaction to improve the durability of the coating; the silicon oxygen bond generated by γ-aminopropyl triethoxysilane and the carboxyl / hydroxyl group in the film-forming resin undergo hydrogen bonding to further enhance adhesion and compatibility.
[0014] Furthermore, the preparation method of the adhesion promoter comprises the following steps: 20-35 parts by weight of a 15-30wt% phytic acid aqueous solution are mixed with 2-5 parts by weight of glycidyl acrylate, and then 0.1-0.3 parts by weight of tetrabutylammonium bromide and 0.03-0.05 parts by weight of hydroquinone are added, and the mixture is reacted at 85-90°C and 200-400rpm for 1-3h, extracted with ethyl acetate, and then the ethyl acetate is recovered by reduced pressure distillation to obtain alkenyl grafted phytic acid; 8-12 parts by weight of hydroxypropyl acrylate, 1-3 parts by weight of isomeric tridecanol polyoxyethylene ether, and 1-2 parts by weight of γ-aminopropyl triethoxysilane are mixed, and 3-6 parts by weight of alkenyl grafted phytic acid are added under nitrogen atmosphere, 70-75°C, and 200-400rpm stirring conditions, and the mixture is stirred for 4-6h, and then 0.5-0.8 parts by weight of water are added and the stirring is continued for 1-2h, and the mixture is cooled to room temperature to obtain an adhesion promoter.
[0015] Preferably, the aqueous dispersant is one of dispersant EDAPLAN®490, dispersant EDAPLAN®516, dispersant EDAPLAN®397, or a mixture of two or more thereof; brand: Mingling, Germany.
[0016] Preferably, the aqueous defoamer is one of defoamer BYK-016, defoamer BYK-012, defoamer BYK-011, or a mixture of two or more thereof; brand: BYK, Germany.
[0017] Preferably, the film-forming aid is one of ethylene glycol ethyl ether, ethylene glycol butyl ether, tripropylene glycol butyl ether, or a mixture of two or more thereof.
[0018] The present invention also provides a method for preparing a water-based printing coating, comprising the following steps: The aqueous resin emulsion, adhesion promoter, aqueous dispersant and water are mixed according to the raw material formula, stirred at 30-40°C and 400-500rpm for 15-30min, then the aqueous defoamer and film-forming aid are added and stirred for 3-8min, and cooled to room temperature to obtain the aqueous printing coating.
[0019] The present invention also provides application of the above-mentioned water-based printing coating in digital inkjet printing.
[0020] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention provides a water-based printing coating and a preparation method thereof, wherein a specific water-based resin emulsion and an adhesion promoter are added to the raw material formula, wherein the water-based resin emulsion is prepared by using a surface-modified silica / alumina composite, amino polyvinyl alcohol and acrylic acid monomers, and the adhesion promoter is prepared by using hydroxypropyl acrylate, isomeric tridecanol polyoxyethylene ether, γ-aminopropyl triethoxysilane and alkenyl grafted phytic acid, thereby further improving the adhesion and wear resistance of the coating, and having the advantages of being green, environmentally friendly and having a good printing effect.
[0021] 2. The water-based resin emulsion prepared by the present invention not only has good adhesion performance, but also significantly improves the wear resistance of the coating through the synergistic effect of multiple mechanisms. Among them, the addition of sodium dodecyl sulfate and polyvinyl pyrrolidone plays the role of dispersant and stabilizer, ensuring the uniform dispersion of each component in the aqueous phase and avoiding the agglomeration of particles. Ammonium persulfate, as an initiator, promotes the polymerization reaction of acrylate monomers to generate a water-based resin emulsion with excellent performance; the emulsion introduces a surface-modified silica / alumina complex to provide a hard filler, enhances the hardness and wear resistance of the coating, and the introduction of amino polyvinyl alcohol enhances the overall structural stability and flexibility of the coating through chemical bonding and cross-linking. The water-based resin emulsion achieves a dual improvement in the adhesion and wear resistance of the coating by simultaneously introducing a surface-modified silica / alumina complex and amino polyvinyl alcohol, and combines the mini-emulsion polymerization method and the formation of a cross-linked network, significantly extending the service life of the product.
[0022] 3. The adhesion promoter used in the present invention is prepared from hydroxypropyl acrylate, isomeric tridecanol polyoxyethylene ether, γ-aminopropyl triethoxysilane and alkenyl grafted phytic acid as raw materials, which can effectively improve the adhesion performance of water-based printing coatings. During the whole process, the components form a complex three-dimensional network structure through chemical bonding and interaction, so that the adhesion promoter can not only firmly adhere to the surface of the substrate, but also can be closely combined with the film-forming resin, thereby further improving the adhesion performance of the water-based coating. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1 This embodiment provides a water-based printing coating, comprising the following raw materials in parts by weight: 60 parts by weight of aqueous resin emulsion, 1.5 parts by weight of adhesion promoter, 1 part by weight of aqueous dispersant, 0.5 parts by weight of aqueous defoamer, 2 parts by weight of film-forming aid, 35 parts by weight of water. The aqueous dispersant is dispersant EDAPLAN® 490; the aqueous defoamer is defoamer BYK-016; the film-forming aid is ethylene glycol ethyl ether.
[0025] The preparation method of the aqueous resin emulsion comprises the following steps: 6.5 parts by weight of polyvinyl alcohol, 3.5 parts by weight of epichlorohydrin and 90 parts by weight of 0.37wt% hydrochloric acid were mixed, stirred at 68°C and 150rpm for 50min, centrifuged and dried to obtain an intermediate; 4 parts by weight of the intermediate, 0.05 parts by weight of tetrabutylammonium bromide and 50 parts by weight of 0.5wt% ammonia water were mixed, and then 20 parts by weight of ethylenediamine were added, stirred at 68°C and 150rpm for 3h, centrifuged and dried to obtain amino polyvinyl alcohol; wherein the viscosity (25°C) of the polyvinyl alcohol is 20-30mPa.s and the alcoholysis degree is 95-90%; 10 parts by weight of tetraethyl orthosilicate, 25 parts by weight of aluminum nitrate and 120 parts by weight of anhydrous ethanol are mixed to obtain a mixed solution, and the mixed solution is added to 180 parts by weight of 16.5wt% ammonia water at 35°C and 600rpm for reaction for 7h, filtered, dried, and then calcined at 500°C for 2.5h to obtain a silica / alumina composite; 6 parts by weight of the silica / alumina composite are mixed with 50 parts by weight of water, stirred at room temperature and 600rpm for 0.5h, and then 1.2 parts by weight of 3-acrylamidopropyl tris(trimethylsiloxy)silane are added, the temperature is raised to 86°C and stirring is continued for 12h, cooled to room temperature, filtered, and dried to obtain a surface-modified silica / alumina composite; 0.3 parts by weight of sodium lauryl sulfate, 0.1 parts by weight of polyvinyl pyrrolidone and 15 parts by weight of water were mixed, and then 3.5 parts by weight of surface-modified silica / alumina composite and 2.5 parts by weight of amino polyvinyl alcohol were added and ultrasonically dispersed for 15 minutes, wherein the power of the ultrasound was 150 W and the frequency was 20 kHz, and then 7 parts by weight of ethyl methacrylate, 3 parts by weight of butyl acrylate and 0.1 parts by weight of ammonium persulfate were added, and the mixture was reacted at 85° C. and in a nitrogen atmosphere for 6 hours to obtain an intermediate material; wherein the average molecular weight of the polyvinyl pyrrolidone was 10,000; Mix 3 parts by weight of acrylic acid, 7 parts by weight of ethyl methacrylate, 2.5 parts by weight of butyl acrylate, 1.5 parts by weight of hydroxypropyl acrylate, 0.5 parts by weight of methacrylamide and 0.2 parts by weight of ammonium persulfate, stir at 78°C and 150 rpm for 30 minutes, then add 20 parts by weight of the intermediate material and continue stirring for 2 hours, cool to room temperature, adjust the pH to neutral, and obtain an aqueous resin emulsion.
[0026] The preparation method of the adhesion promoter comprises the following steps: Mix 30 parts by weight of a 20wt% phytic acid aqueous solution with 3.5 parts by weight of glycidyl acrylate, then add 0.2 parts by weight of tetrabutylammonium bromide and 0.04 parts by weight of hydroquinone, react at 86°C and 300rpm for 2h, extract with ethyl acetate, and then recover the ethyl acetate by reduced pressure distillation to obtain alkenyl-grafted phytic acid; mix 10 parts by weight of hydroxypropyl acrylate, 2 parts by weight of isomeric tridecyl alcohol polyoxyethylene ether E1340, and 1.2 parts by weight of γ-aminopropyltriethoxysilane, add 5 parts by weight of alkenyl-grafted phytic acid under nitrogen atmosphere, 72°C, and 300rpm stirring conditions, stir for 5h, then add 0.6 parts by weight of water and continue stirring for 1.5h, cool to room temperature, and obtain an adhesion promoter.
[0027] This embodiment provides a method for preparing a water-based printing coating, comprising the following steps: The aqueous resin emulsion, adhesion promoter, aqueous dispersant and water were mixed according to the raw material formula, stirred at 35° C. and 450 rpm for 20 min, then the aqueous defoamer and film-forming aid were added and stirred for 5 min, and cooled to room temperature to obtain the aqueous printing coating.
[0028] Example 2 This embodiment provides a water-based printing coating, comprising the following raw materials in parts by weight: 55 parts by weight of aqueous resin emulsion, 1 part by weight of adhesion promoter, 0.7 parts by weight of aqueous dispersant, 0.3 parts by weight of aqueous defoamer, 1 part by weight of film-forming aid, 30 parts by weight of water. The aqueous dispersant is dispersant EDAPLAN® 490; the aqueous defoamer is defoamer BYK-016; the film-forming aid is ethylene glycol ethyl ether.
[0029] The preparation method of the aqueous resin emulsion is the same as that of Example 1.
[0030] The preparation method of the adhesion promoter is the same as that of Example 1.
[0031] This embodiment provides a method for preparing a water-based printing coating, comprising the following steps: The aqueous resin emulsion, adhesion promoter, aqueous dispersant and water were mixed according to the raw material formula, stirred at 30° C. and 400 rpm for 30 min, then the aqueous defoamer and film-forming aid were added and stirred for 8 min, and cooled to room temperature to obtain the aqueous printing coating.
[0032] Example 3 This embodiment provides a water-based printing coating, comprising the following raw materials in parts by weight: 65 parts by weight of aqueous resin emulsion, 2 parts by weight of adhesion promoter, 1.2 parts by weight of aqueous dispersant, 0.6 parts by weight of aqueous defoamer, 3 parts by weight of film-forming aid, 40 parts by weight of water. The aqueous dispersant is dispersant EDAPLAN® 490; the aqueous defoamer is defoamer BYK-016; the film-forming aid is ethylene glycol ethyl ether.
[0033] The preparation method of the aqueous resin emulsion is the same as that of Example 1.
[0034] The preparation method of the adhesion promoter is the same as that of Example 1.
[0035] This embodiment provides a method for preparing a water-based printing coating, comprising the following steps: The aqueous resin emulsion, adhesion promoter, aqueous dispersant and water were mixed according to the raw material formula, stirred at 40° C. and 500 rpm for 15 minutes, then the aqueous defoamer and film-forming aid were added and stirred for 3 minutes, and cooled to room temperature to obtain the aqueous printing coating.
[0036] Comparative Example 1 The difference between this comparative example and Example 1 is that the preparation method of the aqueous resin emulsion is different, which is as follows: the preparation method of the aqueous resin emulsion comprises the following steps: 10 parts by weight of tetraethyl orthosilicate, 25 parts by weight of aluminum nitrate and 120 parts by weight of anhydrous ethanol are mixed to obtain a mixed solution, and the mixed solution is added to 180 parts by weight of 16.5wt% ammonia water at 35°C and 600rpm for reaction for 7h, filtered, dried, and then calcined at 500°C for 2.5h to obtain a silica / alumina composite; 6 parts by weight of the silica / alumina composite are mixed with 50 parts by weight of water, stirred at room temperature and 600rpm for 0.5h, and then 1.2 parts by weight of 3-acrylamidopropyl tris(trimethylsiloxy)silane are added, the temperature is raised to 86°C and stirring is continued for 12h, cooled to room temperature, filtered, and dried to obtain a surface-modified silica / alumina composite; 0.3 parts by weight of sodium lauryl sulfate, 0.1 parts by weight of polyvinyl pyrrolidone and 15 parts by weight of water were mixed, and then 3.5 parts by weight of surface-modified silica / alumina composite was added and ultrasonically dispersed for 15 minutes, wherein the power of the ultrasound was 150 W and the frequency was 20 kHz, and then 7 parts by weight of ethyl methacrylate, 3 parts by weight of butyl acrylate and 0.1 parts by weight of ammonium persulfate were added, and the mixture was reacted at 85° C. and nitrogen atmosphere for 6 hours to obtain an intermediate material; wherein the average molecular weight of the polyvinyl pyrrolidone was 10000; Mix 3 parts by weight of acrylic acid, 7 parts by weight of ethyl methacrylate, 2.5 parts by weight of butyl acrylate, 1.5 parts by weight of hydroxypropyl acrylate, 0.5 parts by weight of methacrylamide and 0.2 parts by weight of ammonium persulfate, stir at 78°C and 150 rpm for 30 minutes, then add 20 parts by weight of the intermediate material and continue stirring for 2 hours, cool to room temperature, adjust the pH to neutral, and obtain an aqueous resin emulsion.
[0037] Comparative Example 2 The difference between this comparative example and Example 1 is that the preparation method of the aqueous resin emulsion is different, which is as follows: the preparation method of the aqueous resin emulsion comprises the following steps: 6.5 parts by weight of polyvinyl alcohol, 3.5 parts by weight of epichlorohydrin and 90 parts by weight of 0.37wt% hydrochloric acid were mixed, stirred at 68°C and 150rpm for 50min, centrifuged and dried to obtain an intermediate; 4 parts by weight of the intermediate, 0.05 parts by weight of tetrabutylammonium bromide and 50 parts by weight of 0.5wt% ammonia water were mixed, and then 20 parts by weight of ethylenediamine were added, stirred at 68°C and 150rpm for 3h, centrifuged and dried to obtain amino polyvinyl alcohol; wherein the viscosity (25°C) of the polyvinyl alcohol is 20-30mPa.s and the alcoholysis degree is 95-90%; 0.3 parts by weight of sodium lauryl sulfate, 0.1 parts by weight of polyvinyl pyrrolidone and 15 parts by weight of water were mixed, and then 2.5 parts by weight of amino polyvinyl alcohol were added and ultrasonically dispersed for 15 minutes, wherein the power of the ultrasound was 150 W and the frequency was 20 kHz, and then 7 parts by weight of ethyl methacrylate, 3 parts by weight of butyl acrylate and 0.1 parts by weight of ammonium persulfate were added, and the mixture was reacted at 85° C. and nitrogen atmosphere for 6 hours to obtain an intermediate material; wherein the average molecular weight of the polyvinyl pyrrolidone was 10000; Mix 3 parts by weight of acrylic acid, 7 parts by weight of ethyl methacrylate, 2.5 parts by weight of butyl acrylate, 1.5 parts by weight of hydroxypropyl acrylate, 0.5 parts by weight of methacrylamide and 0.2 parts by weight of ammonium persulfate, stir at 78°C and 150 rpm for 30 minutes, then add 20 parts by weight of the intermediate material and continue stirring for 2 hours, cool to room temperature, adjust the pH to neutral, and obtain an aqueous resin emulsion.
[0038] Comparative Example 3 The difference between this comparative example and Example 1 is that the preparation method of the aqueous resin emulsion is different, which is as follows: the preparation method of the aqueous resin emulsion comprises the following steps: 10 parts by weight of tetraethyl orthosilicate, 25 parts by weight of aluminum nitrate and 120 parts by weight of anhydrous ethanol were mixed to obtain a mixed solution, and the mixed solution was added to 180 parts by weight of 16.5 wt% ammonia water at 35° C. and 600 rpm for reaction for 7 hours, filtered, dried, and then calcined at 500° C. for 2.5 hours to obtain a silicon dioxide / aluminum oxide composite; 0.3 parts by weight of sodium lauryl sulfate, 0.1 parts by weight of polyvinyl pyrrolidone and 15 parts by weight of water were mixed, and then 3.5 parts by weight of silicon dioxide / aluminum oxide composite and 2.5 parts by weight of polyvinyl alcohol were added and ultrasonically dispersed for 15 minutes, wherein the power of the ultrasound was 150 W and the frequency was 20 kHz, and then 7 parts by weight of ethyl methacrylate, 3 parts by weight of butyl acrylate and 0.1 parts by weight of ammonium persulfate were added, and the mixture was reacted at 85° C. and nitrogen atmosphere for 6 hours to obtain an intermediate material; wherein the average molecular weight of the polyvinyl pyrrolidone was 10000; Mix 3 parts by weight of acrylic acid, 7 parts by weight of ethyl methacrylate, 2.5 parts by weight of butyl acrylate, 1.5 parts by weight of hydroxypropyl acrylate, 0.5 parts by weight of methacrylamide and 0.2 parts by weight of ammonium persulfate, stir at 78°C and 150 rpm for 30 minutes, then add 20 parts by weight of the intermediate material and continue stirring for 2 hours, cool to room temperature, adjust the pH to neutral, and obtain an aqueous resin emulsion.
[0039] Comparative Example 4 The difference between this comparative example and Example 1 is that the preparation method of the aqueous resin emulsion is different, which is as follows: the preparation method of the aqueous resin emulsion comprises the following steps: 6.5 parts by weight of polyvinyl alcohol, 3.5 parts by weight of epichlorohydrin and 90 parts by weight of 0.37wt% hydrochloric acid were mixed, stirred at 68°C and 150rpm for 50min, centrifuged and dried to obtain an intermediate; 4 parts by weight of the intermediate, 0.05 parts by weight of tetrabutylammonium bromide and 50 parts by weight of 0.5wt% ammonia water were mixed, and then 20 parts by weight of ethylenediamine were added, stirred at 68°C and 150rpm for 3h, centrifuged and dried to obtain amino polyvinyl alcohol; wherein the viscosity (25°C) of the polyvinyl alcohol is 20-30mPa.s and the alcoholysis degree is 95-90%; 6 parts by weight of silica and 50 parts by weight of water were mixed, stirred at room temperature and 600 rpm for 0.5 h, then 1.2 parts by weight of 3-acrylamidopropyltris(trimethylsiloxy)silane was added, the temperature was raised to 86° C., stirring was continued for 12 h, cooled to room temperature, filtered, and dried to obtain surface-modified silica; wherein the average particle size of the silica was 50-100 nm; 0.3 parts by weight of sodium lauryl sulfate, 0.1 parts by weight of polyvinyl pyrrolidone and 15 parts by weight of water were mixed, and then 3.5 parts by weight of surface-modified silica and 2.5 parts by weight of amino polyvinyl alcohol were added and ultrasonically dispersed for 15 minutes, wherein the power of the ultrasound was 150 W and the frequency was 20 kHz, and then 7 parts by weight of ethyl methacrylate, 3 parts by weight of butyl acrylate and 0.1 parts by weight of ammonium persulfate were added, and the mixture was reacted at 85° C. and in a nitrogen atmosphere for 6 hours to obtain an intermediate material; wherein the average molecular weight of the polyvinyl pyrrolidone was 10,000; Mix 3 parts by weight of acrylic acid, 7 parts by weight of ethyl methacrylate, 2.5 parts by weight of butyl acrylate, 1.5 parts by weight of hydroxypropyl acrylate, 0.5 parts by weight of methacrylamide and 0.2 parts by weight of ammonium persulfate, stir at 78°C and 150 rpm for 30 minutes, then add 20 parts by weight of the intermediate material and continue stirring for 2 hours, cool to room temperature, adjust the pH to neutral, and obtain an aqueous resin emulsion.
[0040] Comparative Example 5 The difference between this comparative example and Example 1 is that the homemade adhesion promoter in Example 1 is replaced by a commercially available adhesion promoter Silok® 6208 (brand: Silok).
[0041] Comparative Example 6 The difference between this comparative example and Example 1 is that the preparation method of the adhesion promoter is different, which is as follows: the preparation method of the adhesion promoter comprises the following steps: Mix 10 parts by weight of hydroxypropyl acrylate, 2 parts by weight of isomeric tridecyl alcohol polyoxyethylene ether E1340, and 1.2 parts by weight of γ-aminopropyltriethoxysilane, add 5 parts by weight of polyphosphoric acid (85% P2O5) under nitrogen atmosphere, 72°C, and 300rpm stirring conditions, stir for 5 hours, then add 0.6 parts by weight of water and continue stirring for 1.5 hours, cool to room temperature, and obtain an adhesion promoter.
[0042] Performance Testing The water-based printing coatings obtained in Examples 1-3 and Comparative Examples 1-6 of the present application were uniformly coated on the surface of a polypropylene substrate, and then cured to form a coating (thickness of 40 μm) and tested. The adhesion test was conducted in accordance with the standard GB / T 9286-2021 (0-5 grades, 5 being the worst), the abrasion resistance test was conducted in accordance with the standard GB / T 1768-2006, and the VOC content test was conducted in accordance with the standard GB / T 23986-2009. The results are shown in Table 1.
[0043] Table 1: Performance test results of water-based printing coatings
[0044] From the above performance test results, it can be seen that the water-based printing coatings prepared in Examples 1-3 have good adhesion and wear resistance, and low VOC content, especially the comprehensive performance of the water-based printing coating in Example 1 is the most outstanding. This is because the present invention significantly improves the adhesion and wear resistance of the water-based printing coating by adopting a specific water-based resin emulsion and an adhesion promoter.
[0045] In comparison, since Comparative Examples 1-6 did not adopt the necessary technical solutions, they were significantly worse than Examples 1-3 in the corresponding performance tests. No specific aqueous resin emulsion was used in Comparative Examples 1-4, and no homemade adhesion promoter was used in Comparative Examples 5-6. It can be seen from the results that this resulted in a decrease in the adhesion and wear resistance of the water-based printing coating. The above experimental results further prove the importance of the technical solutions defined in the present invention for its technical effects.
[0046] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A water-based printing coating, characterized in that: It includes the following raw materials in parts by weight: 55-65 parts by weight of aqueous resin emulsion, 1-2 parts by weight of adhesion promoter, 0.7-1.2 parts by weight of aqueous dispersant, 0.3-0.6 parts by weight of aqueous defoamer, 1-3 parts by weight of film-forming aid, and 30-40 parts by weight of water; the adhesion promoter is prepared from hydroxypropyl acrylate, isomeric tridecanol polyoxyethylene ether, γ-aminopropyl triethoxysilane and alkenyl grafted phytic acid.
2. The water-based printing coating according to claim 1, characterized in that: The preparation method of the adhesion promoter comprises the following steps: 20-35 parts by weight of phytic acid aqueous solution are mixed with 2-5 parts by weight of glycidyl acrylate, and then 0.1-0.3 parts by weight of tetrabutylammonium bromide and 0.03-0.05 parts by weight of hydroquinone are added, heated for reaction, extracted, and distilled under reduced pressure to obtain alkenyl grafted phytic acid; 8-12 parts by weight of hydroxypropyl acrylate, 1-3 parts by weight of isomeric tridecyl alcohol polyoxyethylene ether, and 1-2 parts by weight of γ-aminopropyl triethoxysilane are mixed, 3-6 parts by weight of alkenyl grafted phytic acid are added under a nitrogen atmosphere, stirred, and then 0.5-0.8 parts by weight of water are added, stirred continuously, and cooled to obtain an adhesion promoter.
3. The water-based printing coating according to claim 2, characterized in that: The preparation method of the adhesion promoter comprises the following steps: 20-35 parts by weight of a 15-30wt% phytic acid aqueous solution are mixed with 2-5 parts by weight of glycidyl acrylate, and then 0.1-0.3 parts by weight of tetrabutylammonium bromide and 0.03-0.05 parts by weight of hydroquinone are added, and the mixture is reacted at 85-90°C and 200-400rpm for 1-3h, extracted with ethyl acetate, and then the ethyl acetate is recovered by reduced pressure distillation to obtain alkenyl grafted phytic acid; 8-12 parts by weight of hydroxypropyl acrylate, 1-3 parts by weight of isomeric tridecanol polyoxyethylene ether, and 1-2 parts by weight of γ-aminopropyl triethoxysilane are mixed, and 3-6 parts by weight of alkenyl grafted phytic acid are added under nitrogen atmosphere, 70-75°C, and 200-400rpm stirring conditions, and the mixture is stirred for 4-6h, and then 0.5-0.8 parts by weight of water are added and the stirring is continued for 1-2h, and the mixture is cooled to room temperature to obtain an adhesion promoter.
4. The water-based printing coating according to claim 1, characterized in that: The preparation method of the aqueous resin emulsion comprises the following steps: 5-8 parts by weight of polyvinyl alcohol, 2-5 parts by weight of epichlorohydrin and 80-100 parts by weight of hydrochloric acid are mixed, heated and stirred, centrifuged and dried to obtain an intermediate; 3-5 parts by weight of the intermediate, 0.03-0.06 parts by weight of tetrabutylammonium bromide and 40-60 parts by weight of ammonia water are mixed, and then 15-25 parts by weight of ethylenediamine are added, heated and stirred, centrifuged and dried to obtain amino polyvinyl alcohol; 8-12 parts by weight of tetraethyl orthosilicate, 20-30 parts by weight of aluminum nitrate and 100-150 parts by weight of anhydrous ethanol are mixed to obtain a mixed solution, and the mixed solution is added to 150-200 parts by weight of aqueous ammonia under stirring conditions for reaction, filtered, dried, and calcined to obtain a silica / alumina composite; 5-7 parts by weight of the silica / alumina composite are mixed with 40-60 parts by weight of water, stirred, and then 1-1.5 parts by weight of 3-acrylamidopropyl tris(trimethylsiloxy)silane are added, the temperature is raised and stirring is continued, cooled, filtered, and dried to obtain a surface-modified silica / alumina composite; 0.2-0.5 parts by weight of sodium lauryl sulfate, 0.08-0.12 parts by weight of polyvinyl pyrrolidone and 10-20 parts by weight of water are mixed, then 2-5 parts by weight of surface modified silicon dioxide / aluminum oxide composite and 1-4 parts by weight of amino polyvinyl alcohol are added for ultrasonic dispersion, and then 6-8 parts by weight of ethyl methacrylate, 2-4 parts by weight of butyl acrylate and 0.05-0.15 parts by weight of ammonium persulfate are added, and heated for reaction under nitrogen atmosphere to obtain an intermediate material; 2-4 parts by weight of acrylic acid, 6-8 parts by weight of ethyl methacrylate, 1-4 parts by weight of butyl acrylate, 1-2 parts by weight of hydroxypropyl acrylate, 0.3-0.8 parts by weight of methacrylamide and 0.1-0.3 parts by weight of ammonium persulfate are mixed, heated and stirred, then 10-30 parts by weight of the intermediate material are added, stirring is continued, and cooling is performed to obtain an aqueous resin emulsion.
5. The water-based printing coating according to claim 4, characterized in that: The preparation method of the aqueous resin emulsion comprises the following steps: 5-8 parts by weight of polyvinyl alcohol, 2-5 parts by weight of epichlorohydrin and 80-100 parts by weight of 0.2-0.5wt% hydrochloric acid are mixed, stirred at 65-70°C and 100-200rpm for 40-60min, centrifuged and dried to obtain an intermediate; 3-5 parts by weight of the intermediate, 0.03-0.06 parts by weight of tetrabutylammonium bromide and 40-60 parts by weight of 0.3-0.6wt% ammonia water are mixed, and then 15-25 parts by weight of ethylenediamine are added, stirred at 65-70°C and 100-200rpm for 2-4h, centrifuged and dried to obtain amino polyvinyl alcohol; 8-12 parts by weight of tetraethyl orthosilicate, 20-30 parts by weight of aluminum nitrate and 100-150 parts by weight of anhydrous ethanol are mixed to obtain a mixed solution, and the mixed solution is added to 150-200 parts by weight of 15-18wt% ammonia water at 30-40°C and 500-700rpm for reaction for 6-8h, filtered, dried, and then calcined at 450-550°C for 2-4h to obtain a silica / alumina composite; 5-7 parts by weight of the silica / alumina composite is mixed with 40-60 parts by weight of water, stirred at room temperature and 500-700rpm for 0.3-0.6h, and then 1-1.5 parts by weight of 3-acrylamidopropyl tris(trimethylsiloxy)silane is added, the temperature is raised to 85-90°C and stirring is continued for 10-15h, cooled to room temperature, filtered, and dried to obtain a surface-modified silica / alumina composite; 0.2-0.5 parts by weight of sodium lauryl sulfate, 0.08-0.12 parts by weight of polyvinyl pyrrolidone and 10-20 parts by weight of water are mixed, and then 2-5 parts by weight of surface-modified silicon dioxide / aluminum oxide composite and 1-4 parts by weight of amino polyvinyl alcohol are added and ultrasonically dispersed for 10-20 minutes, wherein the power of the ultrasound is 100-200 W and the frequency is 20-30 kHz, and then 6-8 parts by weight of ethyl methacrylate, 2-4 parts by weight of butyl acrylate and 0.05-0.15 parts by weight of ammonium persulfate are added, and the mixture is stirred at 80-90 °C for 24 hours. 0°C, react for 5-8h under nitrogen atmosphere to obtain an intermediate material; 2-4 parts by weight of acrylic acid, 6-8 parts by weight of ethyl methacrylate, 1-4 parts by weight of butyl acrylate, 1-2 parts by weight of hydroxypropyl acrylate, 0.3-0.8 parts by weight of methacrylamide and 0.1-0.3 parts by weight of ammonium persulfate are mixed, stirred at 75-80°C and 100-200rpm for 20-40min, then 10-30 parts by weight of the intermediate material are added and stirring is continued for 1-3h, cooled to room temperature, and the pH is adjusted to neutral to obtain an aqueous resin emulsion.
6. The water-based printing coating according to claim 1, characterized in that: The aqueous dispersant is one of dispersant EDAPLAN®490, dispersant EDAPLAN®516, dispersant EDAPLAN®397, or a mixture of two or more thereof.
7. The water-based printing coating according to claim 1, characterized in that: The aqueous defoamer is one of defoamer BYK-016, defoamer BYK-012, defoamer BYK-011, or a mixture of two or more thereof.
8. The water-based printing coating according to claim 1, characterized in that: The film-forming aid is one of ethylene glycol ethyl ether, ethylene glycol butyl ether, tripropylene glycol butyl ether, or a mixture of two or more thereof.
9. The method for preparing a water-based printing coating according to any one of claims 1 to 8, characterized in that: The following steps are involved: The aqueous resin emulsion, adhesion promoter, aqueous dispersant and water are mixed according to the raw material formula, stirred at 30-40°C and 400-500rpm for 15-30min, then the aqueous defoamer and film-forming aid are added and stirred for 3-8min, and cooled to room temperature to obtain the aqueous printing coating.
10. Use of the water-based printing coating according to any one of claims 1 to 8 in digital inkjet printing.
Citation Information
Patent Citations
Environment-friendly high-strength polyaniline composite coating and preparation method thereof
CN109082202A
High gloss water-based coating applicable to glass surface
GB202413964D0
Eco-friendly semi-non-flammable vibration control paint composition and method of manufacturing the same
KR102637358B1
Anticorrosive Grafted Graphene Filler for Organic Coating and Methods of Preparing the Same
US20200239708A1
KR20230016105A
Cited By
Water-based paint for printing film as well as preparation method and application of water-based paint
CN120737684A